EFEKTIVITAS MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP PEMAHAMAN KONSEP MATA PELAJARAN EKONOMI SISWA KELAS XII IPS DI SMA NEGERI 3 KOTA JAMBI - Pulungan, Putri Adelina; Sari, Pratiwi Indah (SJEE (Scientific Journals of Economic Education), 2022)
This study aims to (1) determine the effectiveness of the conventional learning model for understanding the concepts of economics subject class XII IPS at SMA Negeri 3 Jambi City, (2) to determine the effectiveness of the flipped classroom learning model for understanding the concept of economics subject for XII IPS class students in SMA Negeri 3 Jambi City, (3) to find out the comparison of the effectiveness of learning using conventional and flipped classroom learning models on understanding the concept of economics subjects for class XII IPS students at SMA Negeri 3 Jambi City. The design in this research is quantitative research, using quasi-experimental methods. The population in this study were students of class XII IPS, with a total sample of 58 students. While the data analysis technique used is ancova analysis technique with the help of the SPSS version 21 program. The results of this study indicate that (1) students' conceptual understanding in economics subjects using conventional models is low, this is evident from the number of students who received low scores at the time of the study, (2) students' conceptual understanding in economics subjects used the Flipped model. Classroom has increased, this is evident from the presentation of the highest score in the experimental class 60 while the control class is 58, (3) there is a very significant difference in students' understanding of concepts before using the Flipped Classroom model and after using the Flipped Classroom model where the largest presentation in the control class ranges from 36 -41 and in the experimental class the largest percentage is in the range of 48-53. Keywords: Flipped Classroom, Concept Understa